Diego de la Hoya, aparejador de Juan del Ribero Rada - Campos Sánchez-Bordona, María Dolores (Estudios humanísticos. Geografía, historia y arte, 1996)
The investigation is based on the Architecture of León, in the XVI century, and the personality of Juan del Ribero Rada and his architect's assistant Diego de la Hoya. Both artists stablish an interesting profesional ralitionship. Trough which, Diego de la Hoya will end being in charge of the contruction of Las Carnicerías , the portal of the collegial church of S. Isidoro and other buildings of the town of León.